Hamstring injuries in professional soccer players: Extent of MRI-detected edema and the time to return to play - Crema, M. D.; Godoy, I. R. B.; Abdalla, R. J.; Sanchez de Aquino, J.; McNeill Ingham, S. J.; Skaf, A. Y. (Sports Health: A Multidisciplinary Approach, 2018)
Background: Discrepancies exist in the literature regarding the association of the extent of injuries assessed on magnetic resonance imaging (MRI) with recovery times. Hypothesis: MRI-detected edema in grade 1 hamstring injuries does not affect the return to play (RTP). Study Design: Retrospective cohort study. Level of Evidence: Level 4. Methods: Grade 1 hamstring injuries from 22 professional soccer players were retrospectively reviewed. The extent of edema-like changes on fluid-sensitive sequences from 1.5-T MRI were evaluated using craniocaudal length, percentage of cross-sectional area, and volume. The time needed to RTP was the outcome. Negative binomial regression analysis tested the measurements of MRI-detected edema-like changes as prognostic factors. Results: The mean craniocaudal length was 7.6 cm (SD, 4.9 cm; range, 0.9-19.1 cm), the mean percentage of cross-sectional area was 23.6% (SD, 20%; range, 4.4%-89.6%), and the mean volume was 33.1 cm3 (SD, 42.6 cm3; range, 1.1-161.3 cm3). The mean time needed to RTP was 13.6 days (SD, 8.9 days; range, 3-32 days). None of the parameters of extent was associated with RTP. Conclusion: The extent of MRI edema in hamstring injuries does not have prognostic value. Clinical Relevance: Measuring the extent of edema in hamstring injuries using MRI does not add prognostic value in clinical practice.